Михайло Осипович Судієнко - український історик, археограф і меценат середини ХІХ століття - Чухно, В. (Сiверянський лiтопис, 2009)
Ця стаття присвячена життю і творчості Михайла Осиповича Судієнка, одного з найвідоміших українських археографів середини XIX століття. У ній приводяться біографічні відомості про самого археографа, членів його сім'ї та про основні етапи його життя: дружбу з О.С. Пушкіним, роботу в Київській комісії для розбору стародавніх актів тощо. Настоящая статья посвящена жизни и творчеству Михаила Осиповича Судиенко, одного из наиболее известных украинских археографов середины XIX века. В ней приводятся биографические сведения о самом археографе, членах его семьи и об основных этапах его жизни: дружбе с А.С. Пушкиным, работе в Киевской комиссии для разбора древних актов и т.д. This article is devoted to the life and creation of Michael Osipovich Sudienko, one of the well - known Ukrainian specialist in the study and publication of early texts in the middle of the 19 the century. Inhere is some biographic information about this specialist, the members of his family and the main facts about his life in it: his close friendly relations with A.S. Pushkin, work in the Kievan commission for analysis of ancient decrees, etc.